Adopting a White-Collar Crime Theoretical Framework for the Analysis of Terrorism: an Explorational Undertaking - Shichor, David (Journal of contemporary criminal justice, 2017)
This article is an exploratory attempt to apply a certain theoretical framework to the criminological analysis of terrorism. It follows an approach that was applied before to the study of white-collar crime in the wake of the recent economic meltdown. In a special issue of Criminology & Public Policy, five causal variables emerged from essays that were dealing with the subprime mortgage crisis. These causal variables were used to analyze certain aspects of radical Islamist terrorism and to explore some possible ways to reduce involvement in the current wave of terrorist activities. The analysis indicates that policies targeting two out the three causal variables for reducing white-collar crime—the supply of lure and the increase in the credibility of external oversight—were seen as having potentials for reducing terrorism as well. However, the potential for promising terrorism reduction policies aiming at the third causal variable—increasing the effectiveness of internal oversight and self-restraint—seems problematic.